Penerapan Pembelajaran Think Pair Share Dilengkapi Ajaran Asah, Asih, Asuh untuk Meningkatkan Motivasi dan Prestasi Belajar Matematika - Nella Evina Marlena; Esti Harini; Denik Agustito (UNION : Jurnal Ilmiah Pendidikan Matematika, 2021)
This study aims to describe the process of learning mathematics using the TPS Learning Model (Think Pair Share) equipped with teachings, compassion, fostering in increasing motivation and learning achievement of mathematics in class VIII A students of SMP N 2 Banguntapan. This research is a kind of class action research (CAR) which is conducted in two cycles. The subjects of this study were eighth grade students of SMP N 2 Banguntapan. Academic Year 2019/2020, the number of students is 30 students. Data collection techniques in this study were carried out with observation techniques, test techniques, and documentation techniques. The results showed the average percentage of students' motivation achievement from pre-cycle of 58.33% increased to 66.11% in the first cycle and 82.78% in the second cycle. While students' mathematics learning achievement can be seen from the average initial ability score of 63.83 to 75.67 in the first cycle and increased to 82.07 in the second cycle.